Adverse Childhood Experiences, Negative Emotionality, and Pathways to Juvenile Recidivism. (November 2017) - Wolff, Kevin T.; Baglivio, Michael T.
Prior work has illustrated youth exposed to adverse parenting practices are more likely to offend and juvenile offenders with maltreatment histories more likely to re-offend. In addition, aggressive tendencies and a hostile interpretation of the actions of others and one's environment increase antisocial behavior. Unfortunately, the pathways by which those effects occur are not well understood. Using a sample of more than 25, 000 juvenile offenders, we use structural equation modeling (SEM) to examine the pathways by which adverse childhood experiences (ACEs) affect juvenile delinquency. Results indicate ACEs have both a direct and indirect effect on recidivism, with nearly half of the total effect of ACEs on re-offending operating through negative emotionality. Policy implications are discussed.